INTERROGATING THE SUCCESSES AND FALIURES OF THE SELEUCID EMPIRE (2020)
The narratives surrounding the Seleucid Empire have been presented by modern historians, and drawing from the works of such ancient authors as Appian, Pliny, Polybius, and Iosephus on the subject matter. These modern scholars namely, Strootman, Houghton and Lorber, Kurt and SherwinWhite among others have discussed the various aspects of the history, culture and structure of the Seleuicid Empire, with little attention paid solely to her attainments and shortcomings. This study attempts to critically interrogate the successes and fiascos of the Empire, with a view to highlighting the workings of the leadership that translated to victories and failures in the Seleucid kingdom. The paper argues that the leaders who were motivated and succeeded in expanding the frontiers ofthe kingdom, in due course, became careless and deficient in employing effective strategic measures in administering the empire, and her weak foreign policies exacerbated the conflicts with allies and foes alike. Further studies may examine allthe wars and peace treaties undertaken bythe Seleucid Empire.